Internet Inquiry. (15th November 2013) - Kingsley, Tara; Tancock, Susan
Abstract This article showcases the online research and comprehension competencies students will need to successfully engage with Internet Inquiry. The Common Core State Standards, the research on new literacies skills, and the future of technology‐based assessments require educators to fully take on the challenges of meaningfully embedding and supporting innovations in authentic, inquiry‐based learning with digital texts. This manuscript focuses on four fundamental competencies that are important for Internet inquiry tasks: 1) generate high‐quality inquiry topics, 2) effectively and efficiently search for information, 3) critically evaluate Internet resources, and 4) connect ideas across Internet texts. A rationale, what it looks like in the classroom, what scaffolds are needed to support and guide students to independence are provided for each competency.